2015
DOI: 10.3390/molecules200610839
|View full text |Cite
|
Sign up to set email alerts
|

A Halogen-Containing Stilbene Derivative from the Leaves of Cajanus cajan that Induces Osteogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: Abstract:A new natural halogen-containing stilbene derivative was isolated from the leaves of Cajanus cajan (L.) Millsp. and identified as 3-O-(3-chloro-2-hydroxyl-propanyl)-longistylin A by comprehensive spectroscopic and chemical analysis, and named cajanstilbene H (1). It is the first halogen-containing stilbene derivative found from plants. In human mesenchymal stem cells (hMSC) from bone marrow, 1 did not promote cell proliferation, but distinctly enhanced osteogenic differentiation of hMSC in time-and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In 2015, Cai et al isolated a halogen-containing stilbene derivative in leaves of Cajanuscajan (L.) Mill sp. They reported this compound has an anti-proliferative effect against cancer cell lines [ 10 ]. One of the hydroxylated stilbene derivatives which is known as Resveratrol and isolated from medicinal plants, was reported as apoptosis-inducing agent, aryl hydrocarbon receptor (AhR) modulator, and human cytochrome P450 (CYP) inhibitor [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Cai et al isolated a halogen-containing stilbene derivative in leaves of Cajanuscajan (L.) Mill sp. They reported this compound has an anti-proliferative effect against cancer cell lines [ 10 ]. One of the hydroxylated stilbene derivatives which is known as Resveratrol and isolated from medicinal plants, was reported as apoptosis-inducing agent, aryl hydrocarbon receptor (AhR) modulator, and human cytochrome P450 (CYP) inhibitor [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [5] isolated a pair of new enantiomers stilbene dimer (+)-and (−)-Cajanusine [(+)-1 and (−)-1] with unique coupling patterns from the leaves of pigeon pea (Cajanus Cajan) (1)(2). Two stilbene compounds, longistylin A and C (3-4) were isolated from the leaves of pigeon pea by Duker-Eshun et al [6] According to the investigation and research of Tao and others, there were 44 stilbene compounds in Leguminosae from 1995 to 2008, [7] cicerfuran (5), [8] pawhuskins A-C (6-8), [9] 5-methoxy-Eresveratrol-3-O-rutinoside (9), [10] 2'-O-demthylbidwillol B, addisofurans A-B (10-12), [11] burttionl D (13), [12] (E)-3,4'-dimethoxy-5-rutinsoyl-stilbene (14), [13] 3,5-dimethoxy-4'-O-(β-rhamnopyranosyl-(1→6)-β-glucopyranoside)stilbene (15), [14] lespedezavirgatol (16), [15] chiricanines A-E (17-21), [16] 4-hydroxy-5'-methoxy-6",6"-dimethylpyran[2",3",3',4"]stilbene (22), 3,5-dimethoxy-4-hydroxy-6",6"-dimethylpyran[2",3",3",4"]-stilbene (23),3,4,5-trimenthoxy-6",6"-dimethylpyran[2",3",3',4"]stilbene (24), [17] macheariols A-B (25-26), [18] [19] cararosinol A (28), [20] (+)-isoampelopsin F (29) and (−)-isoampelopsin F (30), caraphenols A-C (31-33), [21] carasinols A-C (34-36), [22] caragaphenol A (37), [23] tibeticanol (38), [24] T-epi,8'epi,11-de-O-methyl-5'-methoxygnetifolin F (39), [25] leachianols C-G (40-44), [26] davidiols A-C (45-47), [27] stenophyllol B (48). [28] In recent years, scholars have done a lot of research on the chemical constituents of pigeon pea.…”
Section: Stilbenes Isolated From Leguminosaementioning
confidence: 99%
“…[28] In recent years, scholars have done a lot of research on the chemical constituents of pigeon pea. Cai et al [29] isolated a new natural halogen-containing stilbene derivative from the leaves of Cajanus cajan (L.) Millsp, and named cajanstilbene H (49). Zhang et al [30,31] reported the isolation, structural elucidation, and cytotoxicities of cajanstilbenoid A, cajanstilbenoid B, cajanotone, cajanamide A (50-53), and other four known stilbenes (54-57).…”
Section: Stilbenes Isolated From Leguminosaementioning
confidence: 99%
See 2 more Smart Citations